A case of intermittent bilious emesis in a term neonate: a case report and brief review of literature - Asha Mudugere; Antaryami Pradhan; Vijay Kumar; Debasish Nanda (SpringerOpen, 2024)
Abstract Background Neonatal intestinal obstruction is a complex condition that poses challenge in management. Prompt recognition and appropriate management are crucial to prevent complications. We present a case of a term neonate with intermittent bilious vomiting. Case presentation The baby underwent routinely performed investigations, including abdominal radiography and ultrasound, which provided inconclusive results. However, contrast-enhanced computed tomography revealed a web at duodenojejunal flexure. Exploratory laparotomy confirmed the diagnosis, and surgical intervention was performed. The baby's postoperative course was prolonged with a gradual transition from parenteral nutrition to enteral feeds. Conclusion This case highlights a rare cause of intestinal obstruction, the unusual location of duodenal web, the importance of maintaining a high index of suspicion for intestinal obstruction, even in the absence of classical signs, and the value of utilizing contrast-enhanced computed tomography when initial investigations are inconclusive.